Dampak Manajemen Perubahan Lingkungan Kerja Masa Pandemi Covid-19 Terhadap Karyawan Balai Teknik Perkeretaapian Kelas II Wilayah Sumatera Bagian Utara - Aulia, Windi; Rahmadhani, Sri (Jurnal Manajemen Akuntansi (JUMSI), 2022)
The Covid-19 pandemic in Indonesia is a disease pandemic (Covid-19) that is ongoing throughout the world. The first positive case of Covid-19 in Indonesia was detected in March 2020, many changes have occurred in Indonesia, especially in the Indonesian economy. New policies are made and implemented by the leadership in order to maintain employee safety. One of them is at tthe Class II Railway Center for the North Sumatra Region so that there is a change in the management of the work environment for its employees,such as maintaining distance,high levels of hygiene,and requiring vaccines.The currentimplementation of PSBB and PPKM requires all companies to make new policies for mutual safety that have an impact on the company and its employees. Based on this, this research was conducted aiming to determine the impact of the management of changes in the work environment through a case study on the Employees of Class II Railways in the North Sumatra Region.